A hazard of lingual orthodontic attachments: a case report. (December 2015) - Oliver, Graham; Borumandi, Farzad
Abstract : A case is presented of an unusual trauma to the floor of mouth caused by an unused lingual orthodontic button. This resulted in a vein being stripped from the floor of mouth and was associated with severe pain and restricted tongue movement. Management was by ligation and excision of the loop of the vessel under local anaesthesia.